2008
DOI: 10.1128/jvi.00766-08
|View full text |Cite
|
Sign up to set email alerts
|

Activation of Akt through gp130 Receptor Signaling Is Required for Kaposi's Sarcoma-Associated Herpesvirus-Induced Lymphatic Reprogramming of Endothelial Cells

Abstract: Kaposi's sarcoma (KS) is the most common tumor of AIDS patients worldwide. KS-associated herpesvirus (KSHV) is the infectious cause of this highly vascularized skin tumor. The main cell type found within a KS lesion, the spindle cell, is latently infected with KSHV and has markers of both blood and lymphatic endothelial cells. During development, lymphatic endothelial cells differentiate from preexisting blood endothelial cells. Interestingly, KSHV infection of blood endothelial cells induces lymphatic endothe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
67
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 59 publications
(69 citation statements)
references
References 61 publications
2
67
0
Order By: Relevance
“…But it also poses an important biological question: is the result solely due to lessened immunosuppression, or does inhibition of mTOR signaling have direct antitumor effects? There is reason to believe that the latter might play a role: studies of both PEL cells and KSHV-infected endothelial cells have shown activation of PI3K and Akt phosphorylation (191,192), both of which are events that occur upstream of mTORC1, the principal target of rapamycin action. Thus, viral infection may turn on the mTORC1 pathway.…”
Section: Ks Clinical Investigation: the Gift That Keeps On Givingmentioning
confidence: 99%
“…But it also poses an important biological question: is the result solely due to lessened immunosuppression, or does inhibition of mTOR signaling have direct antitumor effects? There is reason to believe that the latter might play a role: studies of both PEL cells and KSHV-infected endothelial cells have shown activation of PI3K and Akt phosphorylation (191,192), both of which are events that occur upstream of mTORC1, the principal target of rapamycin action. Thus, viral infection may turn on the mTORC1 pathway.…”
Section: Ks Clinical Investigation: the Gift That Keeps On Givingmentioning
confidence: 99%
“…VEGFR3 mRNA is upregulated 6-fold in KSHV-infected TIME cells compared to mock-infected cells ( Fig. 2A), as we have described previously (20,23). We next examined the protein expression levels of both Ets-1 and VEGFR3 using Western blot analysis.…”
Section: Ets-1 Is Highly Expressed In the Ks Tumormentioning
confidence: 93%
“…Interestingly, expression of the lymphatic-specific VEGFR3 gene was also knocked down by Ets-1 siRNA in KSHV-infected cells. We previously reported that activation of gp130 by KSHV is required for lymphatic reprogramming and for the expression of lymphatic-specific Prox-1, podoplanin, LYVE-1, and VEGFR3 genes (23). Knockdown of gp130 by siRNA results in a decrease in VEGFR1, VEGR3, and podoplanin but does not significantly alter the expression levels of Ets-1 (Fig.…”
Section: Figmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, the Kaposi sarcoma herpes virus depends on the JAK2/STAT3 pathway for Prox-1-mediated lymphatic reprogramming of ECs. 28 On the other hand, the loss of Prox-1 activity results in defective lymphangiogenesis. 13,14 In a murine contact hypersensitivity model, downregulation of Prox-1 is inversely correlated with local TNF and interferon-γ production.…”
Section: Discussionmentioning
confidence: 99%